Conversas entre deficiência e educação : por uma política da interdependência nos cotidianos escolares - Abreu, Gabriela Vieira de (2019)
This work aims to problematize the connexion between disability and education, in the processes of constructing an inclusive education. The research is based on work experiences in everyday education, as a practice of mediation work in regular schools in the city of Niterói / RJ as well as through the Continuing Education of Teachers of Special Education of Youth and Adult Education / EJA, in the city of Vitória / ES. In the research, daily emerges as the trigger for analyzes of how inclusive processes have been constituted, as well as their effects on the lives of students and teachers and the school itself. In the construction of the research we use the methodology of the research journals as articulated by the French Institutional Analysis. We analyze that with the access of disabled students to regular schools, educational practices are stressed. By traversing them, we first understand that separating disabled students from nondisabled students, each in their specific schools, is a practice of discrimination; in its most radical form. Then, analyzing the inclusive developments in the school day-to-day, we estimate that there are different ways of knowing how to do inclusion. Many of them still hold discriminatory perspectives on disability, aiming to maintain a standardized school format. How do we partner with other practices? How to cultivate practices that escape discriminatory processes? As interlocutors, that go through the entire research process, we highlight the Disability Studies, seeking to observe the ethical guideline of the motto "nothing about us, without us", which is established and central for the practices of work and research. Which indicates that any practice around disability, needs to be woven in partnership with disabled people. Finally, this research has as working direction the ethical-political exercise that involves the cultivation of interdependence. For this, we will discuss with work tactics that we consider important to access our interdependent condition. They are the exercise of care, preserving the dimension of autonomy, and of the conversation preserving the dimension of not knowing,as modes of access and affirmation of otherness, in the acceptance of the infinite diversity of the world.